Desenvolvimento de aplicativo para configuração de relés de distância comerciais - Cruz, Leonardo de Andrade (2023)
Transmission lines are the components of the electrical system with the highest rate of occurrence of faults. This is due to its exposure to climatic conditions in large extensions of territory. Several protection functions are used for the protection of these transmission lines, but the most outstanding function is the distance protection function performed by the relays, which is a protection designed especially for transmission lines. This function is formed by protection zones, which are defined by adjustments, which specify the zone size and the actuation time. Protection relays have curve models for this function and each relay manufacturer has its standard and parameters to perform the adjustments. The relays used in this work were GE L90, SEL 311L and SIEMENS 7SL86. For the development of this work, only the MHO curve was used. The developed application uses the Python programming language to run the entire algorithm. The user enters the desired system parameters and with this information, he can run the algorithm, which generates graphs with information, such as currents, voltages and MHO curves, according to the fault and the manufacturer of the desired relay. The application is an important tool that can assist in analysis, decision-making, learning and testing for students and professionals in the field of protection.